Delay in the treatment of cancer. Study of 1000 cases - Lazo Flores, Eduardo (1965)
It has made the study of time elapsed between the time they first looked at the National Institute of Neoplastic Diseases and the time they began receiving specific treatment in 1000 consecutive patients seen between January and June 1962; which accounted for 6.1 percent of the 16,349 patients admitted in 1962 . In 1000 patients admitted to the Institute , 1114 final diagnoses were made , as became a diagnosis in some patients. 72.5 percent of patients were female and 27.5 percent male. Factors park them ( summer or winter ) do not substantially influence the type of patients seen at the Institute or the delay for treatment. The 58.6 percent of cases ( 653 ) were treated as outpatients , 26.7 percent of cases ( 297) were hospitalized and 14.7 percent were referred to other health care facilities . In 653 cases ( 58.6 % of all cases) of patients were treated as outpatients , 441 cases were out of sight before starting appropriate treatment and 212 cases specific treatment began . 653 final diagnoses , in which 75 were malignant neoplasms , benign neoplasms 197 , 6 ​​precancerous , 19 miscellaneous , nonneoplastic 253 , and 103 observations were made . The average number of days elapsed between the date of the first query in the Admissions and date of the start of treatment in the group of cases referred to the above conclusion , was 18 days.